2022
DOI: 10.3389/fped.2022.828637
|View full text |Cite
|
Sign up to set email alerts
|

Current Practice of Fluid Maintenance and Replacement Therapy in Mechanically Ventilated Critically Ill Children: A European Survey

Abstract: Appropriate fluid management in mechanically ventilated critically ill children remains an important challenge and topic of active discussion in pediatric intensive care medicine. An increasing number of studies show an association between a positive fluid balance or fluid overload and adverse outcomes. However, to date, no international consensus regarding fluid management or removal strategies exists. The aim of this study was to obtain more insight into the current clinical practice of fluid therapy in mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…There is no consensus about the initiation of restrictive fluid management after both adult and pediatric cardiac surgery because there have been no randomized controlled trials [16]. In critically ill pediatric patients, randomized clinical trials do not exist [17][18][19]. The above-discussed measures in preventing FO need to be validated in well-designed prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus about the initiation of restrictive fluid management after both adult and pediatric cardiac surgery because there have been no randomized controlled trials [16]. In critically ill pediatric patients, randomized clinical trials do not exist [17][18][19]. The above-discussed measures in preventing FO need to be validated in well-designed prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study, of 85 children post-cardiac surgery, reported a relationship between fluid accumulation, edema, and duration of MV ( 21 ); however, edema was measured by a radiologist’s assessment of chest wall thickness rather than by clinical assessment of the patient. Pediatric intensivists consider edema to be an important factor in fluid management ( 22 ) despite a lack of clinical tools to quantify it.…”
Section: Discussionmentioning
confidence: 99%
“…This makes fluid overload one of the most frequent complications encountered in the pediatric intensive care unit (PICU). In a recent survey by the European Society of Pediatric and Neonatal Intensive Care (ESPNIC) virtually all of the 107 participating PICU clinicians considered fluid overload to be a major unmet medical health problem [5]. Recently, the Australian and New Zealand Intensive Care Society Paediatric Study Group considered studies focused on restrictive fluid therapy even a top research priority [6].…”
Section: Introductionmentioning
confidence: 99%